Belief in the Hereafter and Iqbal’s Concept of Eternity: An Analytical Study (Al-Qamar, 2023)
Belief in the Hereafter is one of the six pillars of Islamic belief required of a Muslim in order to complete his faith.  Although the general conception of life after death and the Hereafter is found in all Divine Religions, the emphasis given in Islam is unique. A glance at the Holy Quran provides the idea that believing in the Hereafter is the most important issue in Islam after believing in God. The topic has covered nearly one third of the Holy Quran with more than 1200 Ayaats. It is almost impossible to find a page in the Quran in which the issue of the Hereafter is not mentioned. Believing in God and the Hereafter are coupled in the Quran approximately 30 times. Therefore, in Islamic Theology, believing in God and the Hereafter are considered the border between atheism and religious belief. Believing in the Hereafter in Islam means the soul and the body of the dead will rise on the Day of Resurrection to be judged. Righteous people will be rewarded with eternal blessings in Paradise while the sinful and disbelievers will suffer in Hell, in following, arguments about hereafter along with Iqbal’s, critique on philosophers and concept of eternity would be discussed.
Keywords: Belief; Hereafter; Holy Quran; Islamic Theology; Believing in God; Philosophers